Situation and development balance of major chronic disease service provision in the Yangtze River Delta of China: a literature- and coupling coordination degree model-based analysis - Yu-cheng QI; Pei-wu SHI; Qun-hong SHEN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the status quo and balanced development of major chronic disease service provision capabilities in the Yangtze River Delta region of China, and to provide a reference for promoting high-quality and balanced development of major chronic disease prevention and control capabilities in the region. MethodsWe retrieved documents on prevention and control of major chronic diseases published by local administrations in the Yangtze River Delta region (including Shanghai municipality and three provinces of Jiangsu, Zhejiang and Anhui) during the period from January 2009 through December 2019. Taking a page from service provision elements for an appropriate public health system, service coverage rate (SCR) and assessable service coverage rate (ASCR) were constructed for quantitative analysis on major chronic disease service provision capability of the municipality and the three provinces in the region. Coupling coordination degree model was adopted to assess the balance of the service provision capacity development in the Yangtze River Delta region. ResultsThe overall SCR and ASCR of major chronic disease service provision for the Yangtze River Delta region increased from 21.2% and 10.0% in 2009 to 82.8% and 51.5% in 2019. In the year of 2019, the prevention level-specific SCR and ASCR were the highest for tertiary prevention; the administrative division-specific SCR of tertiary prevention was the highest (96.0%) for Shanghai municipality and the lowest (71.0%) for Anhui province, while, the administrative division-specific ASCR of tertiary prevention was the highest (71.0%) for Jiangsu province and the lowest (33.0%) for Zhejiang province. The overall index value for coupling coordination degree of SCR and ASCR of the Yangtze River Delta region increased from 38.97 and 11.58 in 2009 to 90. 73 and 70.72 in 2019; the overall scores of 2019 for the balance of SCR of primary, secondary and tertiary prevention in the region were 9, 9 and 10, and the overall scores for the balance of ASCR were 7, 7 and 8 respectively. ConclusionIn the Yangtze River Delta region during the period of 2009 - 2019, the major chronic disease service provision capacity and the balance for the capacity development increased yearly; the service provision capacity was higher for tertiary prevention than that for primary and secondary prevention and the development balance was higher for SCR than that for ASCR.